John Henry Newman: faith, reason and education (Memorandum: Memória e História em Psicologia, 2017)
This issue is a contribution about John Henry Newman’s thought on faith, reason and education. These dimensions are strictly linked together, not only because Newman’s conversion from Anglicanism to Catholicism (1845) is the result of a path of faith, that is considered by himself as an act of implicit reason (and reason is something greater than the evidences of logic), but also because the assent the faith requires is the result of “cumulation of probabilities”: faith, since it’s not an idea but a living faith, can develop within life and culture and, as he explains in The Idea of a University, means not only a reason rightly exercised, that corresponds to liberal education of gentleman, but also catholic faith, because, according to him, “liberal” means not “indifferentism”, but “catholic”.